2023
DOI: 10.1371/journal.pone.0294024
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for DEprescribing and Care to reduce Antipsychotics in Dementia (DECADE)–A hybrid effectiveness-implementation pilot study

Kirstine Skov Benthien,
Laura Victoria Jedig Lech,
Hanne Birke
et al.

Abstract: Introduction Behavioural and psychological symptoms of dementia (BPSD) should only rarely and briefly be treated with antipsychotics. Despite recommendations to the contrary, the use of antipsychotics in nursing home residents with dementia is widespread and followed by serious adverse effects. Intervention studies on methods to reduce the use of antipsychotics in persons with dementia are few and needed. The aim of this protocol is to describe the rationale and content of the intervention DEprescribing and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In this aspect, hand messages have been considered a non-pharmacological intervention consisting of potential benefits that help to reduce the stress levels. A pilot study has been performed that involves that patients with dementia who have reported a decrease in their agitation process (Benthien et al 2023). The study has also confirmed that there could be several beneficial effects on the hospitalized patients who are suffering from dementia.…”
Section: Analysis and Discussionmentioning
confidence: 82%
“…In this aspect, hand messages have been considered a non-pharmacological intervention consisting of potential benefits that help to reduce the stress levels. A pilot study has been performed that involves that patients with dementia who have reported a decrease in their agitation process (Benthien et al 2023). The study has also confirmed that there could be several beneficial effects on the hospitalized patients who are suffering from dementia.…”
Section: Analysis and Discussionmentioning
confidence: 82%
“…The current study serves as a pre-study to the DECADE project (Deprescribing and Care to reduce Antipsychotics in Dementia) carried out prior to launching the full-scale intervention as described in detail elsewhere, 19 to inform the content of the intervention and implementation. The aim was to explore healthcare professionals' experiences of caring for nursing home residents with dementia and the use of antipsychotics, and to explore interpretations potentially influencing their use.…”
Section: Introductionmentioning
confidence: 99%